Selected Papers from the 19th International Conference on Micro- and Nano-Technology for Power Generation and Energy Conversion Applications (Power MEMS 2019) - Knapkiewicz, Paweł; Walczak, Rafał (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
As users, we require more and more reliable and longer operation of electronic devices. Most often, the efforts of scientists and engineers related to energy management, energy conversion, and energy storage are overlooked. The PowerMEMS slogan in its meaning hides the science of materials enabling the construction of modern accumulators and batteries, so important for the developing consumer electronics and electromobility; energy harvesters used wherever conventional power sources cannot be used; and finally the methods and algorithms of energy processing and management that increase the efficiency of the devices they operate. This Special Issue contains six research papers selected from those presented at the 19th International Conference on Micro and Nanotechnology for Power Generation and Energy Conversion Applications (Power MEMS 2019), as and representative of all papers presented during the Conference.